Crack onset assessment near the sharp material inclusion tip by means of modified maximum tangential stress criterion - Ondrej Krepl; Jan Klusák (Fracture and Structural Integrity)
In the case of particle reinforced composites, where the particles are in a form of sharp material inclusions, singular stress concentration exists on each tip of each inclusion. This is due to the geometric and material discontinuities between matrix and particle. These points of stress concentration are susceptible of crack initiation and thus often responsible for failure of the whole structure. The modified maximum tangential stress criterion is employed in order to predict crack onset conditions.